Filmar para tajar: Madrid en el cine en torno al 15-M - Luis Deltell Escolar (Cahiers de Civilisation Espagnole Contemporaine, 2022)
This article examines the portrayal of the city of Madrid through the films and audiovisual productions that emerged as a result of the 15-M movement. An analysis is made of the productions by the artistic collectives that emerged as a response to the first demonstrations by the protesters, followed by an overview of the works of established filmmakers who approached this topic and, finally, the aesthetic and thematic evolution of the subsequent films by these creators is explored. The main hypothesis is that these films attempt to interpret recent history –especially the Spanish Transition– and the city of Madrid not as a neutral or peaceful place, but as a space where conflict and struggle take place. The filmmakers analyzed film in order to sever or break away from traditional interpretations of history and the city.